Inserting professionals and professional organizations in studies of wrongdoing: The nature, antecedents and consequences of professional misconduct. (November 2019) - Gabbioneta, Claudia; Faulconbridge, James R; Currie, Graeme; Dinovitzer, Ronit; Muzio, Daniel
Professional misconduct has become seemingly ubiquitous in recent decades. However, to date there has been little sustained effort to theorize the phenomenon of professional misconduct, how this relates to professional organizations, and how this may contribute to broader patterns of corruption and wrongdoing. In response to this gap, in this contribution we discuss the theoretical and empirical implications of analyses that focus on the nature, antecedents and consequences of professional misconduct. In particular, we discuss how the nature of professional misconduct can be quite variegated and nuanced, how boundaries between and within professions can be either too weak or too strong and lead to professional misconduct, and how the consequences of professional misconduct can be less straightforward than normally assumed. We also illuminate how some important questions about professional misconduct are still pending, including: how we define its different organizational forms; how it is instigated by the changing nature of professional boundaries; and how its consequences are responded to in professional organizations and society more widely.